The Very Hungry Caterpillar's Rainbow Colors - Carle, Eric (New York : World of Eric Carle, an imprint of Penguin Random House LLC, 2023)
"In this delightful board book with rainbow-colored edges, young readers will experience a different vibrant shade on each spread. Find the red ladybug, the green tree, and more in this bright book featuring fun things in every color of the rainbow!"--.
new kids book 2025 winter.
Ages 0-3
Keywords: Colors -- Juvenile literature